Out of School Learning Environments in Social Studies Education: A Phenomenological Research with Teacher Candidates - TOPCU, Ersin (Canadian Center of Science and Education, 2017)
In this study, it was aimed to determine the remarks of teacher candidates on the place and importance of out of school learning environments in Social Studies education. Phenomenological method, which is one of the qualitative research designs, was used in this study. The work group of the study consists of 73 teacher candidates who conduct out of school activities (43 of them are Social Studies teacher candidates and 31 of them are Classroom teacher candidates). Semi structured interview form was used as data collection tool. Activity phase of the study was conducted in museums, Islamic-Ottoman social complexes, castles and historic mosques in Kastamonu, Sakarya, Kars and Eregli (a district of Zonguldak). Gathered data of the study was examined by using content analysis method, and it was presented with cause and effect relation. When results of the study were evaluated, it was concluded that teacher candidates believe that out of school learning activities embody the knowledge and increase memorability by integrating learning into living. Besides, according to teacher candidates, there are many obstacles ahead of out of school activities particularly economic reasons and reluctance of teachers and the structure/content of Social Studies lesson is very suitable for such activities.
Keywords: 4. Education